2023
DOI: 10.3748/wjg.v29.i5.815
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 among patients with liver disease

Abstract: Coronavirus disease 2019 (COVID-19) is primarily a respiratory disease with multi-organ involvement, including impaired liver function. It has been noticed that a significant proportion of COVID-19 patients have liver dysfunction, especially those with a more severe disease course. The coronavirus causes direct damage to the liver using the angiotensin-converting enzyme 2, a cell-surface receptor for cellular entry, that is expressed in the liver. According to previous research, liver enzyme abnormalities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 87 publications
1
3
0
1
Order By: Relevance
“…Additionally, a meta-analysis conducted by Khoury et al reported risk ratios of 1.9 for overall mortality among cancer patients [ 32 ]. Similarly, in our study, patients with solid tumors or end-stage chronic liver disease had significantly increased risks for the severe courses, consistent with findings from previous studies [ 32 , 33 ]. Although patients with hematologic diseases and end-stage chronic kidney disease also showed a trend towards increased risk for severe outcomes, this did not reach significance, probably due to the smaller sample size for these less prevalent diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a meta-analysis conducted by Khoury et al reported risk ratios of 1.9 for overall mortality among cancer patients [ 32 ]. Similarly, in our study, patients with solid tumors or end-stage chronic liver disease had significantly increased risks for the severe courses, consistent with findings from previous studies [ 32 , 33 ]. Although patients with hematologic diseases and end-stage chronic kidney disease also showed a trend towards increased risk for severe outcomes, this did not reach significance, probably due to the smaller sample size for these less prevalent diseases.…”
Section: Discussionsupporting
confidence: 93%
“…COVID-19 has been associated with liver injury, even in patients without pre-existing liver conditions [23] . The extent of liver injury in COVID-19 cases is generally mild [24] and is more pronounced in males, older adults, and people with high body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Of the approximately 1700 patients with chronic liver disease at an Italian liver unit, by transitioning to a telecare model of care, none were reported to have contracted COVID‐19 5 . This is an important finding because liver dysfunction in COVID‐19 patients is a risk factor for severe illness and death 40 …”
Section: Hepatologymentioning
confidence: 99%